2016
DOI: 10.1177/0142723716678383
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the semantic functions of but in middle childhood: The role of text- and sentence-level comprehension abilities

Abstract: We examined Italian 7-to 9-year-olds' understanding of the connective but when used to relate two events in sentences embedded in short stories. Performance was largely accounted for by the cognitive complexity of the sentence that included the connective and the salience of its meaning (confirmed in a second study with adults). Additional influences on children's performance were the category of the story in which the critical sentence was embedded and the child's text comprehension abilities. Further, by 9 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The raw score was the sum of correct answers (max score 14). Cronbach's alpha for the present sample was acceptable (.61) and in line with values reported for primary school children (Florit, Cain, & Levorato, ).…”
Section: Methodssupporting
confidence: 89%
“…The raw score was the sum of correct answers (max score 14). Cronbach's alpha for the present sample was acceptable (.61) and in line with values reported for primary school children (Florit, Cain, & Levorato, ).…”
Section: Methodssupporting
confidence: 89%
“…The acquisition of discourse connectives is a long and complex process that starts between the ages of 2 and 3 (e.g., Bloom, Lahey, Hood, Lifter, & Fiess, 1980; Evers‐Vermeul & Sanders, 2009; Zufferey, 2010) and continues into the adult years (e.g., Zufferey & Gygax, 2020a). A large body of studies across different languages has analyzed various aspects of the acquisition of connectives during childhood (e.g., for English: Cain & Nash, 2011; Crosson, Lesaux, & Martinello, 2008; Irwin & Pulver, 1984; McClure & Geva, 1983; for Finnish: Pyykkönen & Järvikivi, 2012; for Italian: Florit, Cain, & Levorato, 2017; for German: Volodina & Weinert, 2020; for Turkish: Oğuz & Özge, 2020), converging to conclude that even connectives used frequently in speech such as because and after are not fully acquired until the end of the primary school years. For instance, Cain and Nash (2011) showed that, in a within‐sentence cloze task, 10‐year‐olds performed less well than adults for temporal connectives ( before , after ), causal connectives ( so , because ), and adversative connectives ( but , although ).…”
Section: Background Literaturementioning
confidence: 99%
“…Whereas the early acquisition of connectives has been the subject of numerous studies (e.g., Cain & Nash, 2011;Florit, Cain, & Levorato, 2017;Pyykkönen & Järvikivi, 2012), the acquisition of connectives that are less common in spoken language and mostly bound to the written modality, such as however and therefore in English, has, to the best of our knowledge, rarely been investigated (though for exceptions see Crosson & Lesaux, 2013;Nippold, Schwartz, & Undlin, 1992;Zufferey & Gygax, 2020a, 2020b). Yet mastering these connectives represents an essential step in achieving effective written communication.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, also the connectives' respective difficulty should be considered. Not only the reader's age but also the context as well as the connectives' semantic class and occurrence frequency have been shown to influence the understanding of connectives (Becker & Musan, 2014;Blything, Davies, & Cain, 2015;Cain, Patson, & Andrews, 2005;Crosson & Lesaux, 2013;Crosson, Lesaux, & Martiniello, 2008;Florit, Cain, & Levorato, 2017;Gardner, 1980;Knoepke et al, 2016;Schuth, Heppt, Köhne, Weinert, & Stanat, 2015). However, it would be beneficial to state these findings more consistently, for example, with respect to defining semantic classes.…”
Section: Limitations and Further Researchmentioning
confidence: 99%